Intronic tRNAs of mitochondrial origin regulate constitutive and alternative splicing - Hoser, Simon M. (Genome Biol, 2020)
BACKGROUND: The presence of nuclear mitochondrial DNA (numtDNA) has been reported within several nuclear genomes. Next to mitochondrial protein-coding genes, numtDNA sequences also encode for mitochondrial tRNA genes. However, the biological roles of numtDNA remain elusive. RESULTS: Employing in silico analysis, we identify 281 mitochondrial tRNA homologs in the human genome, which we term nimtRNAs (nuclear intronic mitochondrial-derived tRNAs), being contained within introns of 76 nuclear host genes. Despite base changes in nimtRNAs when compared to their mtRNA homologs, a canonical tRNA cloverleaf structure is maintained. To address potential functions of intronic nimtRNAs, we insert them into introns of constitutive and alternative splicing reporters and demonstrate that nimtRNAs promote pre-mRNA splicing, dependent on the number and positioning of nimtRNA genes and splice site recognition efficiency. A mutational analysis reveals that the nimtRNA cloverleaf structure is required for the observed splicing increase. Utilizing a CRISPR/Cas9 approach, we show that a partial deletion of a single endogenous nimtRNA(Lys) within intron 28 of the PPFIBP1 gene decreases inclusion of the downstream-located exon 29 of the PPFIBP1 mRNA. By employing a pull-down approach followed by mass spectrometry, a 3′-splice site-associated protein network is identified, including KHDRBS1, which we show directly interacts with nimtRNA(Tyr) by an electrophoretic mobility shift assay. CONCLUSIONS: We propose that nimtRNAs, along with associated protein factors, can act as a novel class of intronic splicing regulatory elements in the human genome by participating in the regulation of splicing. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13059-020-02199-6.